(untitled) (Economic and Political Thought, 2015)
The crisis of the European Union or the crisis of European integration? This dilemma, seemingly contradictory, is the subject of the analysis in this article. The author tries to prove the thesis that today we are facing a crisis of the EU, which entails a crisis of European integration. According to the author, even if the European Union broke up, nobody and nothing would be able to stop the process of European integration, at most it might be slowed down. At the same time, the author emphasizes here that 2014, and particularly dramatic events in Ukraine, the Middle East and North Africa show that the ‘end of the history’, in which people believed after the fall of communism in Europe was an illusion. Triumphalism and the hope for eternal peace have ended, and the belief in the gradual but inevitable democratization of the following countries and societies has been strongly undermined. Peace and security of Europe and the world are today – according to the author – seriously threatened. Eleven years after the great enlargement of the EU in 2004, its numerous shortcomings have been revealed and its role and prestige in the international arena have weakened. The author is trying to answer the questions why it happened and what should be done to prevent the EU from disintegration.